Gender Identity and Gender Role in DSD Patients Raised as Females: A Preliminary Outcome Study - Ercan, Oya; Kutlug, Seyhan; Uysal, Omer; Alikasifoglu, Mujgan; Inceoglu, Derya (Frontiers in Endocrinology, 2013)
Gender identity and gender role are expected to be consistent with gender assignment for optimal DSD management outcome. To our knowledge, our study is the first to attempt evaluation of gender related outcomes in Turkish DSD patients. After receiving institutional ethical board approval and subject (or parent) informed consent, subjects with DSD raised as girls (22 patients 46 XX DSD,11 patients 46XY DSD) answered 566 questions of the Minnesota Multiphasic Personality Inventory (MMPI) questionnaire including 60- item Masculinity-Femininity (MF) subscale which was the focus in this study. Controls (n:50) were females similar to the probands in age, level of education, relationship status and having a job or not also answered all questions. The answers were evaluated by a trained psychologist(D.I.) on MMPI . For statistical purposes, 7 findings were obtained from the data related to the MF subscale from the patients and controls. Of these 7 findings (S1-S7), two were associated with masculinity (S3-S4) and another two were associated with femininity (S5-S6) In DSD patients, the percentages of masculinity findings were significantly higher when compared to controls (p< 0.001 and p< 0.001 for S3 and S4 respectively). In controls, the percentages of femininity findings were significantly higher when compared to DSD females (p< 0.001 and p< 0.001 for S5 and S6 respectively).There was no significant difference between 46XX DSD patients and 46XY DSD patients with respect to the percentage of any of the 7 findings. Two patients requested gender change to male;only these two patients had the finding stating that sexual impulses could come to existence as actions(S7). In conclusion efforts to identify modifiable factors with negative impact and thus modifying them, and professional guidance may be important in minimizing the encountered gender related problems in DSD patients